2013
DOI: 10.1021/pr301200e
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of New Biomarkers for Identifying and Monitoring Kidney Disease and Their Translation into a Rapid Mass Spectrometry-Based Test: Evidence of Presymptomatic Kidney Disease in Pediatric Fabry and Type-I Diabetic Patients

Abstract: Using label-free quantative proteomics, we have identified 2 potential protein biomarkers that indicate presymptomatic kidney disease in the urine of pediatric patients with type-I diabetes and Fabry disease (n = 20). Prosaposin and GM2 activator protein (GM2AP) were observed to be elevated in the urine of these patient groups compared to age- and sex-matched controls. These findings were validated by development of a rapid MRM-based tandem mass spectrometry test. Prosaposin was observed to be both significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…Moreover, another advantage of using urine, instead of blood, is its easy and non‐invasive collection that allows repeated sampling for disease monitoring. In the last years, several studies have been performed, in urines, aiming to identify biomarkers that can detect early stages of DN and progressive kidney function decline in diabetic patients, as well as biomarkers that can allow for a non‐invasive diagnosis of kidney disease (Chang et al ., ; Chu et al ., ; Manwaring et al ., ; Merchant et al ., ; Lewandowicz et al ., ; Siwy et al ., ; Vitova et al ., ; Wheelock et al ., ).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Moreover, another advantage of using urine, instead of blood, is its easy and non‐invasive collection that allows repeated sampling for disease monitoring. In the last years, several studies have been performed, in urines, aiming to identify biomarkers that can detect early stages of DN and progressive kidney function decline in diabetic patients, as well as biomarkers that can allow for a non‐invasive diagnosis of kidney disease (Chang et al ., ; Chu et al ., ; Manwaring et al ., ; Merchant et al ., ; Lewandowicz et al ., ; Siwy et al ., ; Vitova et al ., ; Wheelock et al ., ).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Another study, involving 10 paediatric Fabry patients, found that, following 12 months of ERT, prosaposin was the only protein significantly reduced and that another GM 2 activator protein was also decreased in urine [56]. …”
Section: Biomarkers and Imaging Findingsmentioning
confidence: 99%
“…Prosaposin and ganglioside GM 2 activator protein were significantly elevated in patients with Fabry disease and ERT was associated with a significant reduction in urinary excretion of these proteins. Therefore, these urinary biomarker models may useful as diagnostic tools for patients with Fabry disease, as well as for monitoring response to ERT [107]. However, there is still work to be done to identify a biomarker that truly reflects disease activity and progression, as well as enabling responses to ERT to be measured.…”
Section: Areas For Further Researchmentioning
confidence: 99%